Comparative politics : the problem of equivalence - Deth, Jan W. van (Routledge, 1998)
This book tackles the issues involved and explores strategies to deal with many of the problems of establishing equivalence. Each contribution focuses on a theoretically relevant theme, such as: tolerance; political values; religious orientations; gender roles; voluntary associations; party organizations and party positions; democratic regimes, and the mass media. Each chapter covers different topics, methods, data and countries, making use of research to show the problems of finding similar or identical indicators in realistic research settings.
Keywords: Comparative government.; POLITICAL SCIENCE -- Government -- Comparative.; POLITICAL SCIENCE -- Reference.; Comparative government; Vergelijkende politicologie.; Institutions politiques comparées.